Zakat and Waqf Institutions in Empowering the Muslim Community’s Economy: Strategic Review and Challenges - selmiana salam selmi; Fitriah Ningsih; Amiruddin.K; Mukhtar Lutfi (Wasīlah: Journal Of Sharia Sciences, 2025)
This study aims to describe the strategic role of zakat and waqf institutions in empowering the Muslim community’s economy and to identify the challenges and optimization strategies in their management. Zakat and waqf are Islamic social finance instruments that function not only as religious obligations but also as mechanisms for wealth distribution and socio-economic development. This research employs a descriptive qualitative approach with data collected through interviews, observation, and documentation. The findings indicate that zakat and waqf institutions have implemented various productive programs that contribute to improving the economic independence of beneficiaries. However, the management of these instruments still faces several challenges, including low public literacy, limited human resource capacity, insufficient digitalization, and lack of institutional synergy and regulatory harmonization. Proposed optimization strategies include system digitalization, human resource development, collaboration with Islamic financial institutions, Islamic social literacy campaigns, and regulatory enhancement with incentives for zakat and waqf contributors. Through these strategies, zakat and waqf can serve as key instruments in building an inclusive, just, and sustainable Islamic economy.